New euprimate postcrania from the early Eocene of Gujarat, India, and the strepsirrhine–haplorhine divergence. Issue 99 (October 2016) - Dunn, Rachel H.; Rose, Kenneth D.; Rana, Rajendra S.; Kumar, Kishor; Sahni, Ashok; Smith, Thierry
Abstract: The oldest primates of modern aspect (euprimates) appear abruptly on the Holarctic continents during a brief episode of global warming known as the Paleocene-Eocene Thermal Maximum, at the beginning of the Eocene (∼56 Ma). When they first appear in the fossil record, they are already divided into two distinct clades, Adapoidea (basal members of Strepsirrhini, which includes extant lemurs, lorises, and bushbabies) and Omomyidae (basal Haplorhini, which comprises living tarsiers, monkeys, and apes). Both groups have recently been discovered in the early Eocene Cambay Shale Formation of Vastan lignite mine, Gujarat, India, where they are known mainly from teeth and jaws. The Vastan fossils are dated at ∼54.5 Myr based on associated dinoflagellates and isotope stratigraphy. Here, we describe new, exquisitely preserved limb bones of these Indian primates that reveal more primitive postcranial characteristics than have been previously documented for either clade, and differences between them are so minor that in many cases we cannot be certain to which group they belong. Nevertheless, the small distinctions observed in some elements foreshadow postcranial traits that distinguish the groups by the middle Eocene, suggesting that the Vastan primates—though slightly younger than the oldest known euprimates—may represent the most primitive known remnants of the divergence between the two great primate clades.